Why is Education Improving? An Economic and Poverty Investigation of Average Length of Schooling in the Context of SDG 4 (Quality Education) in East Java 2015-2024 - Rohmatul Insaniyah; Muhammad Abdul Ghofur; Heny Musfida; Dhiah Fitrayati; Dani Dwi Saputra (Journal of Psychology and Culture Behavior in SDGs, 2026)
Objective: The low quality of education in Indonesia ranks 12th out of 12 countries in Asia according to a survey by PERC, and East Java Province is still below the mandatory 9-year education standard based on data from BPS of 8.69 years in 2024. Therefore, this study aims to analyze the effect of Gross Regional Domestic Product (GRDP) and poverty levels on the average length of schooling in East Java Province during the period 2015–2024. Method: The method used in this study is multiple linear regression or Ordinary Least Square (OLS) analysis through SPSS to see the relationship between the two economic variables and the community's educational attainment. The data used is secondary data from the Central Statistics Agency, which covers regional educational development and economic conditions.  Results: The results show that GRDP and poverty levels simultaneously have a significant effect on average length of schooling, with an explanatory contribution of 76%. However, partially, both variables have a negative effect, indicating that economic growth is not yet evenly distributed and poverty remains an obstacle to improving education. This study is expected to provide input for local governments in formulating policies to improve the quality of education. Novelty: The novelty of this study lies in the analysis of the partial and simultaneous effects of two major economic factors on education indicators at the regional level, which has not been empirically studied much previously. Therefore, this study supports SDG 4 (Quality Education) by ensuring inclusive and equitable quality education and promoting lifelong learning opportunities.